Mechanical properties of non-centrosymmetric CePt3Si and CePt3B. (4th April 2017) - Rogl, G; Legut, D; Sýkora, R; Müller, P; Müller, H; Bauer, E; Puchegger, S; Zehetbauer, M; Rogl, P
Abstract: Elastic moduli, hardness (both at room temperature) and thermal expansion (4.2–670 K) have been experimentally determined for polycrystalline CePt3 Si and its prototype compound CePt3 B as well as for single-crystalline CePt3 Si. Resonant ultrasound spectroscopy was used to determine elastic properties (Young's modulus E and Poisson's ratio ν ) via the eigenfrequencies of the sample and the knowledge of sample mass and dimensions. Bulk and shear moduli were calculated from E and ν, and the respective Debye temperatures were derived. In addition, ab initio DFT calculations were carried out for both compounds. A comparison of parameters evaluated from DFT with those of experiments revealed, in general, satisfactory agreement. Positive and negative thermal expansion values obtained from CePt3 Si single crystal data are fairly well explained in terms of the crystalline electric field model, using CEF parameters derived recently from inelastic neutron scattering. DFT calculations, in addition, demonstrate that the atomic vibrations keep almost unaffected by the antisymmetric spin–orbit coupling present in systems with crystal structures having no inversion symmetry. This is opposite to electronic properties, where the antisymmetric spin–orbit interaction has shown to distinctly influence features like the superconducting condensate of CePt3 Si.